Catalytic Enantioselective Synthesis of anti‐Vicinal Silylboronates by Conjunctive Cross‐Coupling. (19th March 2020) - Meng, Yan; Kong, Ziyin; Morken, James P.
Abstract: Chiral 1, 2‐bimetallic reagents are useful motifs in synthetic chemistry. Although syn ‐1, 2‐bimetallic compounds can be prepared by alkene dimetallation, anti ‐1, 2‐bimetallics are still rare. The stereospecific 1, 2‐metallate shift that occurs during conjunctive cross‐coupling is shown to enable a practical and modular approach to the catalytic synthesis of enantioenriched anti ‐1, 2‐borosilanes. In addition to reaction development, the synthetic utility of anti ‐1, 2‐borosilanes was investigated, including applications to the synthesis of anti ‐1, 2‐diols and anti ‐1, 2‐amino alcohols Abstract : Über Kreuz mit dem Nachbarn : Enantioselektive, katalytische, konjunktive Kreuzkupplungen mit gut verfügbaren Silylalkenylboronsäureestern eröffnen einen direkten Zugang zu anti ‐vicinalen Silylboronsäureestern. Diese bieten ein vielseitiges Hilfsmittel für den Aufbau 1, 2‐difunktioneller organischer Bausteine. Boc= tert ‐Butoxycarbonyl, Bz=Benzoyl; mac=Dimethyldihydroacenaphtho.